Inovasi Program Podcast sebagai Media Komunikasi Berbasis Teknologi Digital pada Pondok Pesantren Mambaus Sholihin 2 Blitar - Asif Faroqi; Fitrah Ramadhani; Dewita Putri; Putri Aprilia Regina; Feni Ella Aries; Prizalia Berliana (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Podcasts are an accessible and popular audio platform that has grown rapidly, especially among the younger generation. Over time, podcasts have developed from initially being audio to now developing in visual form, making the message easier to understand and not boring for listeners. This research aims to determine the innovation of the podcast program as a digital technology-based communication medium at the Mambaus Sholihin 2 Blitar Islamic Boarding School. This research uses the theory of Cook, Irwin and Matthew (2009) that the factors determining the success of innovation are determined by Leadership, Management/Organization, Risk Management, Human Capital and Technology. The methods used are observation, interviews and documentation. Data analysis was carried out using the Miles and Huberman method with data reduction steps, data presentation and drawing conclusions. The research results show that this digital technology-based innovation has become a strategic step in utilizing broadcasting facilities. Even though they were faced with various challenges, such as limited filming and editing facilities, as well as the need to improve technical skills, the KKN group together with the podcast team succeeded in showing good adaptation and high commitment to continuing to learn and develop.